Analysis of double walled carbon nanotube structured badminton racket - Vidya Sagar, K.; Goutam, B.; Chandra, K. V.; Chary, S. N. (AIP Conference Proceedings 2327, 2021)
Nanotube structures deflection sensitivity is a significant parameter to design a badminton racket with rugged structure. Badminton racket have been developed using titanium alloys, fibre glass and carbon fibres. The structural deformation tends to collapse is significant during swing while smashes the shuttle. This paper focused to identify the right structured material for maximum load changes. Double walled carbon nanotube is considered for analyzing structural behaviour using Finite Element Modelling (FEM ) ap proach. The analy sis is applied on Zig-Zag, Armchair and chiral nanotubes. With different tube radius of the double walled carbon naotube, the mechanical characteristics of Bending Stiffness, modulus of elasticity, and moment of inertia are estimated. Variable force is applied on the tube structure which influences on the mechanical characteristics. The elastic beam elements behaviour between the carbon nanotube structures are studied using FEM analysis the results attained are reasonably good with applied load.